Effect of dentinal surface preparation on bond strength of self-etching adhesive systems - Rocha, Patricia Itocazo [UNESP]; Borges, Alessandra Bühler [UNESP]; Rodrigues, José Roberto [UNESP]; Arrais, César Augusto Galvão [UNESP]; Giannini, Marcelo (FapUNIFESP (SciELO), 2006)
The aim of this study was to evaluate the effects of dentin surface treatments on the tensile bond strength (TBS) of the self-etching primer Clearfil SE Bond (CSE) and the one-step self-etching One-Up Bond F (OUB). The exposed flat dentin surfaces of twenty-four sound third molars were prepared with diamond bur at high-speed, carbide bur at low-speed or wet ground with #600 grit SiC paper. The adhesive systems were applied to the dentin surfaces and light-cured according to the manufacturers' instructions. A 6-mm high composite crown was incrementally built-up and each increment was light-cured for 40 seconds. After being stored in water (37°C/24 h), the samples were serially sectioned parallel to the long axis, forming beams (n = 20) with a cross-sectional area of approximately 0.8 mm 2. The specimens were tested in a Universal Testing Machine at 0.5 mm/min. The cross-sectional area was measured and the results (MPa) were analyzed by two-way ANOVA and Tukey Test (p < 0.05). Overall, the groups treated with CSE exhibited the highest TBS for all surface treatments. Dentin surfaces prepared with carbide bur at low speed reduced TBS in the CSE group; however, OUB was not affected by surface treatments. The effect of surface abrasive methods on TBS was material-dependent.
Keywords: Dentin; Dentin-bonding agents; Tensile strength; adhesive agent; Clearfil SE Bond; dentin bonding agent; methacrylic acid derivative; One Up Bond F; One-Up-Bond F; resin cement; chemistry; dental acid etching; dental bonding; dentin; drug effect; human; materials testing; shear strength; Acid Etching, Dental; Adhesives; Dental Bonding; Dentin-Bonding Agents; Humans; Materials Testing; Methacrylates; Resin Cements; Shear Strength